2004
DOI: 10.1161/01.hyp.0000148499.54730.0d
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain, Ethnicity, and Sympathetic Nervous System Activity

Abstract: Abstract-Several studies have demonstrated that blacks have heightened pressor sensitivity in response to the ␣-agonist, phenylephrine. However, studies examining whether psychosocial factors contribute to this difference are scarce. We examined the effects of job strain on pressor sensitivity in 76 whites and 46 blacks who were enrolled in a study of stress, sleep, and blood pressure. Responses to phenylephrine were examined at an inpatient clinical research center. After a 3-minute baseline period, a 100-mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 50 publications
1
33
1
3
Order By: Relevance
“…34,[268][269][270][271][272][273][274] This is an important consideration because it may be possible to use clinical 109 and public health interventions 92 to reduce this burden, thereby narrowing health disparities. Second, social and economic stresses lead to a biological wear and tear, or allostatic stress response, [275][276][277][278][279][280] involving a number of pathways, including stimulation of stress hormones, [280][281][282] inflammation, 283 endothelial dysfunction, thrombosis, vascular hyperreactivity, 270,274,[284][285][286][287] and metabolic disturbances. 270,285,288,289 Third, the effects of socioeconomic disadvantage in utero and in early childhood have long-term anatomical and physiological effects that lead to CVD in adulthood.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…34,[268][269][270][271][272][273][274] This is an important consideration because it may be possible to use clinical 109 and public health interventions 92 to reduce this burden, thereby narrowing health disparities. Second, social and economic stresses lead to a biological wear and tear, or allostatic stress response, [275][276][277][278][279][280] involving a number of pathways, including stimulation of stress hormones, [280][281][282] inflammation, 283 endothelial dysfunction, thrombosis, vascular hyperreactivity, 270,274,[284][285][286][287] and metabolic disturbances. 270,285,288,289 Third, the effects of socioeconomic disadvantage in utero and in early childhood have long-term anatomical and physiological effects that lead to CVD in adulthood.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…While the answer to that question is enormously complicated, tantalizing data are accumulating. Subjects who are in low control jobs have blunted baroreflex sensitivity; that is, when their BP increases, they fail to make the appropriate adjustments of HR (25). Other studies have demonstrated that workers with low job control respond to stressors in the laboratory environment with increased fibrinogen (26).…”
Section: Chronic Stressorsmentioning
confidence: 99%
“…Except for five studies on the DCS model (152,160,172,173,179), the studies included in this review controlled for at least one potential confounder. Potential confounders were sociodemographic (age, gender, ethnicity), socioeconomic (education, income, occupation), lifestyle risk factors (smoking, alcohol or caffeine consumption, physical activity, stressful situations, personality traits), biological risk factors (body mass index, waist circumference, known history of CVD, diabetes, medication for hypertension, menopausal status, estrogen medication, pregnancy history, sodium intake, cholesterol), and other factors (marital status, number of children, posture, stress outside work, having eaten a meal, length of time in the current job, and social support at work and outside work).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Confounding biases also need to be addressed. The five studies on the DCS model (152,160,171,173,179) that did not control for any cofactors are the most prone to confounding bias. Confounding might also be present in other studies due to a lack of control for cardiovascular risk factors.…”
Section: (Tables A-c)mentioning
confidence: 99%